A study on the effectiveness of technology transfer towards the work performance in SME‘s - Mohd Hafiz, Abdul Mutalif (2013)
This study was conducted to evaluate the effectiveness of technology transfer in small medium enterprise (SME‘s) manufacturing-based industry. Besides that, the objective of this research is to study the relationship between technology transfer and the work performance. In addition, this study attempt to recommend the best practice of technology transfers for a better work performance. Sets of questionnaires were developed and the data was collected by mail and hand distributed. Total sample of 75 respondents was used in this study. The result of this study showed that the effectiveness level of technology transfer that is used in that industry is good enough. Besides, the relationship between technology transfer and the work performance in terms of quantity of work and quality of work shows there are a strong positive relationship for both variables. Hence, there are lists of several recommendation of best practice of technology transfer for a better work performance in the end of this study.